KOMPETENSI UMUM (GENERIC COMPETENCIES) YANG DIPERLUKAN PENYULUH PERTANIAN - Arifin, Zainal (Fakultas Sains dan Teknologi UIN ALauddin, 2011)
This study aimed at revealing the Ideal Generic Competencies (IGC) needed based on the expert judgement, and the Agriculture Extension Worke ( AEWs) experience.. The data were collected through interview and questionnaire methods, and analysed using the descriptive technique and profile analysis. The result of the descriptive analysis are as the followings. The profile of generic competencies needed by AEWs according to the experts judgement and the document analysis are shown at the rank of Language and communication, Planning and organizing activities, Scientific and technological understanding, Problem solving, Personal and interpersonal, Mathematics, and Cultural understanding. Six of those generic competencies are most important categories, but that Cultural understanding is important category. Language and communication, Planning and organizing activities, Scientific and Technological understanding, and Problem solving were validated in field. This implied that those generic competencies are crucial for AEWs to do the job of an agricultural extension well, so that the competency standard, and the educational and training curriculum are deviced in relevance with them.Â Key words:profile, generic competencies, agriculture, extension worker.